Dr. Christabel Aba Sam and Dr. Christine Vogt-William on Masculine Representations in Ghanaian Afrobeats and Literature - Aba Sam, Christabel; Vogt-William, Christine (Cluster Conversations, 2024)
Dr. Christabel Aba Sam is a Senior Lecturer in the Department of English at the University of Cape Coast, Ghana and currently a Cluster fellow at the University of Bayreuth. In this episode of the Cluster Conversation, she talks with her host Dr. Christine Vogt-William (Director of the Cluster of Excellence’s Gender and Diversity Office) about her work on images of masculinities in Ghanaian Afrobeats and how they reveal certain social politics of contemporary Ghanaian society.